ANALYSIS AND DESIGN OF RISK MANAGEMENT SYSTEM OF ELECTRONIC GOVERNMENT (E-GOVERNMENT) (STUDY CASE: XYZ INSTITUTIONS) - Juliharta, I Gede Putu Krisna; Dewi, Putri Anugrah Cahya; Widiari, Ni Putu (Jurnal TAM (Technology Acceptance Model), 2023)
Electronic-Based Government System or SPBE is a government administration that utilizes information and communication technology to provide services to users. XYZ Institutions is one of the cities implementing SPBE. The implementation of SPBE management by the XYZ Institutions Government received the lowest score and Risk Management was an indicator of SPBE management with a low level of maturity. Risk management is an effort or attempt to control, manage and control risk within an organization. This study conducted an analysis and design of risk management documents at the XYZ Institutions, using the PANRB Regulation Number 5 of 2020 concerning SPBE Risk Management Guidelines as standardization. This research also uses the 2018 ISO 31000 principle approach regarding risk management standards and uses the PDCA method.